A Site-Specific Need Assessment for Ocean Incineration at the North Atlantic Incineration Site (NAIS) - MacDonald, Lynne H. (DigitalCommons@URI, 1989)
This thesis examines the problems of hazardous wastes in the United States-and the problems their disposal present, in particular. Ocean incineration, one of the very few methods available to destroy many highly toxic wastes, is presented as a viable, necessary means to destroy liquid organochlorine wastes. Next, the international and federal regulations governing ocean incineration and the current status of ocean incineration in the United States are reviewed. A site-specific assessment for determining the need for ocean incineration is developed as an alternative to the two currently contended approaches (nationwide versus permit-by-permit need assessments). This site-specific need assessment evaluates the need for ocean incineration in an area surrounding a potential ocean incineration loading port. Thus, the assessment reflects the wastes, and the environment that will be affected by ocean incineration's use from that loading port. Using the EPA's proposed North Atlantic Incineration (NAIS) and the Port of Philadelphia, a site selection methodology - to determine the area where such a need assessment should be performed - and a method for performing the actual need assessment are presented. Based on this study's findings, it is recommended that the proposed site-selection and site-specific need assessment processes be incorporated into the Ocean Incineration program, public awareness programs be expanded, and research and development of ocean incineration and other waste management technologies are continued.